Exploring food neophobia towards new food trends among public university students in Penang - Tarmazi, Siti Anis Adilah; Abdul Mutalib, Sarah Ayuni; Safri, Sarah Ardini; Umar, Norazah; Mohamed Idris, Aida Khalida (Journal of Islamic, Social, Economics and Development, 2025)
Malaysia’s diverse culinary heritage and its openness to sustainable food trends inspire the creation of innovative food products. As competition in food trends intensifies, it is essential for producers to develop creative and appealing foods that cater to consumer preferences while minimising food neophobia. This research seeks to identify the relationship between sensory responsiveness, psychological factors, and food neophobia towards new food trends of innovative foods among public university students in Penang. This study adopted a quantitative approach. The study involved administering a detailed questionnaire via Google Forms to public university students in Penang. The obtained data were analysed using SPSS Version 26. A Pearson correlation analysis conducted showed that there is a weak positive relationship between sensory responsiveness and food neophobia towards new food trends, and a moderate positive relationship between psychological factors and food neophobia. The findings suggest strategies addressing psychological barriers can significantly reduce food neophobia, encouraging students to embrace new food trends. This approach ensures a deeper connection with consumer preferences, driving better acceptance of innovative food products.